2010
DOI: 10.1590/s0103-50532010000400023
|View full text |Cite
|
Sign up to set email alerts
|

Differential metabolic and biological profiles of Lychnophora ericoides mart. (Asteraceae) from different localities in the Brazilian "campos rupestres"

Abstract: Este artigo descreve a caracterização por CLAE-DAD-EM/EM e CLAE-DEC dos perfis de metabólitos secundários de extratos das folhas de Lychnophora ericoides Mart. de diferentes procedências e suas propriedades citotóxicas e antioxidantes. Extratos foliares de populações representando sete diferentes localidades foram avaliados quanto à atividade antioxidante pelo sistema DPPH e à atividade citotóxica em três linhagens tumorais. Os extratos foram eletroquimicamente caracterizados por CLAE-DEC e seus metabólitos se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
(101 reference statements)
1
8
0
3
Order By: Relevance
“…Sesquiterpene lactones are the main compounds employed for Vernonieae systematics [33]. Recent phytochemical investigations have suggested that not all Lychnophora species can store or produce sesquiterpene lactones [34]. An example of a chromatogram with the numbers of the identified signals is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sesquiterpene lactones are the main compounds employed for Vernonieae systematics [33]. Recent phytochemical investigations have suggested that not all Lychnophora species can store or produce sesquiterpene lactones [34]. An example of a chromatogram with the numbers of the identified signals is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This increase was found to be correlated with maximal cytotoxic activities of plants growing at the interface between two types of forest, the campos rupestris and a semi-deciduous forest9. Vicenin-2 was also found to be present in every sample analyzed of L. ericoides , suggesting the conserved accumulation of this secondary metabolite and that there may be a conserved role for this substance9. We therefore set out to identify a physiological role for vicenin-2 mapping its location in the leaves from Brazilian wild Lychnophora plants by subjecting sectioned leaves for Imaging Mass Spectrometry (IMS), and to correlate its tissue distribution with possible physiological functions.…”
mentioning
confidence: 85%
“…In a similar ecological study with Lychnophora ericoides from eight different provenances showed an increase in defensive metabolites (by sesquiterpene lactones biosynthesis). This increase was found to be correlated with maximal cytotoxic activities of plants growing at the interface between two types of forest, the campos rupestris and a semi-deciduous forest9. Vicenin-2 was also found to be present in every sample analyzed of L. ericoides , suggesting the conserved accumulation of this secondary metabolite and that there may be a conserved role for this substance9.…”
mentioning
confidence: 87%
“…2386 between two types of vegetation (and consequently of fauna) could be stimulated to amplify the production and storage of defensive secondary metabolites. This hypothesis can be strengthened by 32 in which is reported that the extract from Ibiraci exhibited the strongest cytotoxic activity in all the evaluated cell lines, while the extracts from the other places presented insignificant or very low cytotoxicity in general. The city of Ibiraci is located in a transition area between two biomes: Cerrado and the semi-deciduous of the Atlantic Forest, while the other populations are located in inner area of the Cerrado.…”
mentioning
confidence: 91%
“…In the other hand, the chlorogenic acids are present in all individual of the evaluated L. ericoides, 17,32 and for this reason, they could be considered as characteristic metabolite for this species; however, the widespread occurrence in Asteraceae family 8,33,34 limits its use as a chemotaxonomic marker.…”
mentioning
confidence: 99%